Connexin43 Expression Increases in the Epithelium and Stroma along the Colonic Neoplastic Progression Pathway: Implications for Its Oncogenic Role - Yusheng Han; Paul J. Zhang; Terina Chen; Sabrina W. Yum; Teresa Pasha; Emma E. Furth (Gastroenterology Research and Practice)
Connexins (Cxs) are critical for normal tissue development, differentiation, and cell proliferation. Normal expression and function of Cxs are considered to play a role in tumor suppression, but abnormal localization and abnormally increased expression of Cxs have been found in a variety of carcinomas. Of the Cx family, Cx43 is a most prevalent member and has been known as a downstream target of β-catenin, a key component of Wnt signaling pathway. We evaluated the expression of Cx43 in the colonic neoplasia progression sequence with additional attention to the stromal component. Resections of 50 colonic adenocarcinomas were stained immunohistochemically for Cx43 on paraffin embedded sections. Cx43 cytoplasmic expression increased progressively in the colonic adenocarcinoma sequence in both the epithelial [normal (4±1), adenomatous (20±2), cancerous (124±10) (P<0.01)], and stromal [normal (19±1), cancerous (45±4) (P<0.01)] components. In the epithelial component, Cx43 was expressed lower in stage I adenocarcinomas (69±12) compared to stage III/IV (158±10, P<0.01). Additionally, Cx43 was relatively increased in the adenocarcinoma at the invasive tumor front in all stages. Cx43 may play a critical role in the pathogenesis of colon cancer via gap junction or other gap junction independent mechanisms such as the Wnt/β-catenin pathway.